2023
DOI: 10.3390/sym15010163
|View full text |Cite
|
Sign up to set email alerts
|

Gait Phase Classification of Lower Limb Exoskeleton Based on a Compound Network Model

Abstract: The classification of lower limb gait phase is very important for the control of exoskeleton robots. In order to enable the exoskeleton to determine gait phase and provide appropriate assistance to the wearer, we propose a compound network based on CNN-BiLSTM. The method uses data from inertial measurement units placed on the leg and pressure sensor arrays placed on the sole as inputs to the model. The convolutional neural network (CNN) is used to obtain the local key features of gait data, and then the bidire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…After calculating the mean absolute error and processing a Bland-Altman analysis, they showed that the differences between both systems are within a mean ± 1.96 standard deviations. Another study [ 63 ] used a passive lower limb weight-bearing exoskeleton equipped with IMUs at the thigh and shank of the exoskeleton. For processing these data, investigators used a CNN-BiLSTM Network Model.…”
Section: Resultsmentioning
confidence: 99%
“…After calculating the mean absolute error and processing a Bland-Altman analysis, they showed that the differences between both systems are within a mean ± 1.96 standard deviations. Another study [ 63 ] used a passive lower limb weight-bearing exoskeleton equipped with IMUs at the thigh and shank of the exoskeleton. For processing these data, investigators used a CNN-BiLSTM Network Model.…”
Section: Resultsmentioning
confidence: 99%
“…The model can accurately identify the four stages in the gait cycle, and the accuracy and F-value are better than other algorithms. Xia et al [ 26 ] used a model based on CNN-BiLSTM to classify seven gait phases of both legs through IMU data of lower limb and plantar pressure data, with a maximum accuracy of 95.09%. Chen et al [ 27 ] proposed a lower-limb exoskeleton gait pattern-recognition method based on LSTM and CNN, which can recognize five common gait patterns with an average recognition accuracy of 97.78%.…”
Section: Introductionmentioning
confidence: 99%